Linking winter conditions to regional disease dynamics in a wild plant–pathogen metapopulation. Issue 3 (10th November 2014) - Penczykowski, Rachel M.; Walker, Emily; Soubeyrand, Samuel; Laine, Anna‐Liisa
Summary: Pathogens are considered to drive ecological and evolutionary dynamics of plant populations, but we lack data measuring the population‐level consequences of infection in wild plant–pathogen interactions. Moreover, while it is often assumed that offseason environmental conditions drive seasonal declines in pathogen population size, little is known about how offseason environmental conditions impact the survival of pathogen resting stages, and how critical the offseason is for the next season's epidemic. The fungal pathogen Podosphaera plantaginis persists as a dynamic metapopulation in the large network of Plantago lanceolata host populations. Here, we analyze long‐term data to measure the spatial synchrony of epidemics and consequences of infection for over 4000 host populations. Using a theoretical model, we study whether large‐scale environmental change could synchronize disease occurrence across the metapopulation. During 2001–2013 exposure to freezing decreased, while pathogen extinction–colonization–persistence rates became more synchronized. Simulations of a theoretical model suggest that increasingly favorable winter conditions for pathogen survival could drive such synchronization. Our data also show that infection decreases host population growth. These results confirm that mild winter conditions increase pathogen overwintering success and thus increase disease prevalence across the metapopulation. Further, we conclude that the pathogen can drive host population growth in the Plantago–Podosphaera system.